Self-Efficacy, Work Motivation, Budgetary Participation, Budget Targets, Accountability and Managerial Performance: Evidence from Aceh, Indonesia - Maulida, Maya; Darwanis, Darwanis; Diantimala, Yossi (Journal of Accounting Research, Organization and Economics, 2021)
Objective This study aims to analyze the role of self-efficacy and work motivation on the relationship between budgetary participation, clarity of budget targets, and accountability with managerial performance in regional work unit in Aceh province, Indonesia. Design/methodology The population in this study was all regional work units in Aceh Province while the samples were drawn from all regional work units of Pidie Regency, Pidie Jaya Regency, and Bireun City which has a total of 147 regional work units. The number of respondents in this study was 441 obtained from the sample of each regional work units which consist of 3 respondents. Results The results showed that budgetary participation, clarity of budget targets, accountability, self-efficacy, and work motivation had an effect on managerial performance in regional work units in Aceh province. Meanwhile self-efficacy moderated the influence of budgetary participation, clarity of budget targets, and accountability on managerial performance and work motivation moderated the influence of budgetary participation, clarity of budget targets, and accountability on managerial performance in regional work units in Aceh province.